A critical review of cognitive behavioural therapy for hoarding disorder: How can we improve outcomes?. (30th August 2021) - David, Jonathan; Crone, Cassandra; Norberg, Melissa M.
Abstract: Psychological treatment for hoarding problems has historically been associated with poor outcomes. When treated as a subgroup of obsessive–compulsive disorder, individuals with hoarding beliefs were less likely to respond to treatment than individuals exhibiting other obsessive–compulsive beliefs and behaviours. When treated as its own disorder using cognitive behavioural therapy, individuals report approximately 25% improvement in symptoms on average. However, less than a third of people experience clinically meaningful change. Further, changes in functioning and quality of life are not routinely assessed. In this paper, we review the current conceptualization and treatment of hoarding problems to shed light on how treatment for hoarding disorder may be improved. Utilizing a harm reduction approach before administering treatment may be important to ensure the safety of individuals. Research should test whether treatment outcomes improve by including strategies that enhance a client's interpersonal functioning and ability to regulate emotions (i.e., based on dialectal behaviour therapy and mentalization‐based treatments), especially while discarding and organizing belongings. We should also use modern learning theory to improve the delivery of exposure activities.